Overview of Mitigation Programs for Cattle Diseases in Austria - Roch, Franz-Ferdinand; Conrady, Beate (Frontiers in Veterinary Science, 2021)
Background: The non-mandatory regulation of animal diseases at the European Union (EU) level enables member states to implement mitigation programs based on their own country-specific conditions such as priority settings of the governments, availability of financial resources, and epidemiological situation. This can result in a heterogeneous distribution of mitigation activities and prevalence levels within and/or between countries, which can cause difficulties for intracommunity trade. This article aims to describe the past, current, and future mitigation activities and associated prevalence levels for four animal diseases, i.e., enzootic bovine leukosis (EBL), infectious bovine rhinotracheitis/infectious pustular vulvovaginitis (IBR/IPV), bovine viral diarrhea (BVD), and bluetongue disease (BT) for Austria. Over a period of 40 years (1978–2020), regulations concerning EBL, IBR/IPV, BVD, and BT were retraced to analyze the changes of legislation, focusing on sampling, testing, and mitigation activities in Austria, and were linked to the collected diagnostic testing results. The study results clearly demonstrate the adoption of the legislation by the Austrian governments in dependency of the epidemiological situations. Furthermore, our study shows that, related to the forthcoming Animal Health Law on April 21, 2021, Austria has a good initial situation to achieve disease-free status and/or free from infection status based on the current available epidemiological situation and previously implemented mitigation activities. The study results presented here are intended to contribute to a better comparison of the eradication status across European countries for cattle diseases by providing information about the mitigation activities and data of testing results over a period of 40 years.